Weight Reduction of Rear Wheel Bracket in FSAE Electric Vehicles Using Topology Optimization - Muhamad Hanhan Nugraha; Muslimin Muslimin; Anes Inda Rabbika; Andy Permana Rusdja; Rezia Asmiati Syifa; Dian Sahril Anwar (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
This research focuses on reducing the weight of the rear wheel bracket in an FSAE electric vehicle prototype using topology optimization. Lightweight vehicle design is critical for improving energy efficiency and reducing environmental impact. The study aims to optimize the bracket's weight while maintaining structural integrity through a systematic approach. The process began with converting the physical bracket into a digital model using precise measurement techniques and SolidWorks software. Finite element analysis was then conducted to evaluate stress distribution under a working force of 5000 N, assuming Aluminium 6061 as the material. Topology optimization was performed to identify and remove low-stress regions, resulting in a 50% weight reduction from 1.2 kg to 0.63 kg without compromising safety. These findings demonstrate the potential of topology optimization to achieve significant weight reductions in electric vehicle components, thereby enhancing battery efficiency and vehicle range. This approach provides valuable insights for the automotive industry in developing more sustainable and efficient designs.